HERMENEUTIKA HUKUM SEBAGAI ALTERNATIF METODE PENEMUAN HUKUM BAGI HAKIM UNTUK MENUNJANG KEADILAN GENDER - Alef Musyahadah Rahmah (Jurnal Dinamika Hukum, 2013)
Hermeneutic law approach can be an effort to make comprehensive interpretation of law, so the contruction of law doesn’t trap to the texts interpretation only. It is going on leaning by the judge in order to judged the case related with victim women that less giving the justice. Hermeneutic law approach consider relevancy between text, context and contextualization is in line with feminist method in understanding and revealing the truth, that is “women’s experience”. The judge will doing uncommon interpretation like applied feminist practical reasoning by doing discussing and listening the unknown in women’s experience. Key words: rechtsvinding, hermeneutics law, judge, gender justice